Spółdzielczość kredytowa typu rolniczego w reformie systemu bankowego z roku 1982 - Ochociński, Stefan (Wydział Prawa i Administracji UAM, 1983)
The article discusses changes in organizational structure and in principles of functioning of cooperative banks which are related to the new banking law and the new cooperative law of 1982 and which will be implemented in practice in the years of 1983 and 1084. The attention is focused on major limitations in the taplemenitation of complete mutual financial aid and of the related rules of cooperative banks as local institutions of small banking credit. The mutual financial aid is limited among others, by the duty on cooperative banks to associate in the State-cooperative owned Bank of the Food Economy as their auditing, organizational and financial central office, this is a channel securing intervention of the State administration in the affairs of credit cooperatives and of the associated individual farmers. Decision-making competence of the centrai Sitate administration in the respect of loaning and other banking «services as well as the directive character of limits and binding guide-lines following from an annual State credit plan are breaking direct links between a credit action and the economic character of local funds of the mutual financial aid. They are also strengthening the effect of administrative measures of directing activities of cooperative banks and weakening cooperative rules and methods of banking influence on individual farmers. Similarly the statutory rules of socializing profits and assimilating cooperative management of earmarked funds to a financial management of state enterprises are decreasing the stimulating role of the mutual financial aid and of the or elated specific cooperative rules. A process of changing statutes of cooperative banks which has begun in 1983 can facilitate the introduction of rules and forms which were described in the end of the article, they can effectuate more complete than previous financial mutual aid of credit cooperatives.
Credit cooperatives of the agricultural type in the reform of banking system of 1982